A Group Desensitization Approach to Public Speaking Anxiety - Akin, Clifford; Kunzman, Glen G. (Canadian Journal of Counselling and Psychotherapy, 2012)
The authors outline a program designed to behaviorally reduce symptoms of public speaking anxiety in university student subjects. Program evaluation shows that a mixed behavioral format emphasizing practice situations produces results similar to traditionally operant or desensitization formats, with less attrition in attendance. Statistically significant changes on fear inventory scores is the measurable objective outcome of the program. In addition, the study indicates that individual desensitization as a supplement to the group program may be clinically helpful for the exceptionally distressed subject, although this was not shown to be statistically significant on the measures employed. Meichenbaum's (1971) finding that "anxiety specific" subjects respond more positively to a behavioral approach than do globally anxious subjects is supported, although not at a statistically significant level. Finally, other factors selected for possible correlation with outcome as measured by fear inventory scores show no relationship.